ANALISIS METODE EVALUASI KINERJA GURU PADA SMP YADIKA 8 JATIMULYA BEKASI - Semuel A. M.; Elsye (Pasca Sarjana Universitas Satya Negara Indonesia, 2016)
Yayasan Abdi Karya (Yadika) is a foundation engaging in education, including the junior high schools or Sekolah Menengah Pertama (SMP). In terms of quality management, Yadika evaluates the teacher performance every year. Supposedly, the results of the evaluation are used to improve the performance of teachers in order to achieve the objectives of education. Yadika implements a rating scale method in the teacher performance assessment. However, the assessment seems intended for administration use only, without clear measures of teaching performance itself. Its measures are mostly used as formal requisites for job promotion and salary adjustments. Due to the weakness of the current method on performance evaluation, therefore, this paper aims to review ways to improve the method. It is suggested the method may include measurement of the real activities of the teacher, such as the class management and teaching skills. Those activities directly improve the teacher’s achievement and quality in line with the education mission of YADIKA.